CCN2 is required for recruitment of Sox2-expressing cells during cutaneous tissue repair - Tsang, Matthew (J Cell Commun Signal, 2014)
Connective tissue growth factor (CTGF/CCN2), a member of the CCN family of matricellular proteins is upregulated in both fibrosis as well as tissue repair. Recently, we showed that, in mice, CCN2 expression by fibroblasts was required for dermal fibrogenesis, but not for cutaneous tissue repair. Lineage tracing analysis linked the ability of CCN2 to promote fibrosis to the requirement for CCN2 to recruit cells expressing the progenitor cell marker Sox2 to fibrotic connective tissue and for differentiating these cells into myofibroblasts. Herein, we show that although loss of CCN2 expression by Sox2-expressing cells does not impair cutaneous tissue repair, CCN2 was required for recruitment of cells derived from Sox2-expressing cells to the wound area. Collectively, these results are consistent with the notion that neither CCN2 nor Sox2-expressing progenitor cells are essential for cutaneous tissue repair and that CCN2 represents a specific anti-fibrotic target.